Certain Correlates of Burnout among Police Personnel in a Metropolitan City of a Developing Country - Anantharaman, Reddiyoor Narayanaswamy (Archives of Business Research, 2014)
Burnout is dysfunctional response to stress. This study investigates the phenomenon of burnout and its relationship to certain demographic, psychological and situational variables. An attempt is also made to find the differences burnout between men and women police. The Maslach Burnout Inventory and demographic profile were administered to a random sample of 220 police personnel in a metropolitan city of a developing country. The results indicated that most of the demographic factors were not related to burnout, however there were significant gender differences in Emotional Exhaustion and Depersonalization dimensions of burnout. Keywords: Burn out, Emotional Exhaustion, Gender difference, Depersonalization.